2011
DOI: 10.1007/s13197-011-0580-0
|View full text |Cite
|
Sign up to set email alerts
|

Compositional, spectroscopic and rheological analyses of mucilage isolated from taro (Colocasia esculenta L. Schott) corms

Abstract: Tropical roots and tubers generally contain mucilage. These mucilages exhibit unique rheological properties with considerable potential as a food thickener and stabilizer. A one-step extraction procedure was used to isolate starch free mucilage and associated proteins from a number of taro (Colocasia esculenta) varieties. The monosaccharide and amino acid composition, the structural and flow properties were investigated. The results showed that yield of mucilage fraction varied from 30 to 190 g.kg(-1). A negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 20 publications
3
40
0
1
Order By: Relevance
“…This suggested a positive interaction between the soluble protein (mostly mucilage in the case of taro, Njintang et al 2011) in raw taro flour favourable to emulsion formation which is degraded in pre-boiled taro flour, but this needs to be investigated. Indeed, the emulsion and foaming of flours are often attributed to proteins which has always been associated with formation of cohesive interfacial film around the air/or oil and water in the mixture system (Njintang et al 2001;Kaur et al 2011).…”
Section: Functional Properties Of Precooked Taro Flourmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested a positive interaction between the soluble protein (mostly mucilage in the case of taro, Njintang et al 2011) in raw taro flour favourable to emulsion formation which is degraded in pre-boiled taro flour, but this needs to be investigated. Indeed, the emulsion and foaming of flours are often attributed to proteins which has always been associated with formation of cohesive interfacial film around the air/or oil and water in the mixture system (Njintang et al 2001;Kaur et al 2011).…”
Section: Functional Properties Of Precooked Taro Flourmentioning
confidence: 99%
“…The most important producers are Nigeria (58 %), Ghana (17 %) and Cameroon (11 %). The corms are low in fat (0.5-1.2 %), proteins (2.9-4.6 %) and vitamins, but are a good source of carbohydrates (90.8-95.5 %) and minerals (1.6-5.5 %) especially magnesium (32.9-382 mg/100 g), calcium (25.4-192 mg/100 g) and potassium (3.5-59.7 mg/100 g) (Aboubakar et al 2008;Kaur et al 2011;Njintang et al 2011). In some areas of the world taro constitutes the main food source; for instance in Palao, Micronesia, taro contributes to about 16 % of the caloric intake (Nip 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucilage, or gum, is generally present in tropical roots and tubers and is particularly abundant in taro. Mucilage has unique rheological properties and holds much potential for use as a food thickener and stabilizer (Njintang et al 2011;Kaushal et al 2013). This natural plant gum also produces gelling effects and increases viscosity (Fedeniuk and Biliaderis 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, mucilage consists of water, pectins, sugars, and organic acids (Misaki et al 1972). In a study investigating mucilage from six different taro varieties, Njintang et al (2011) reported that the carbohydrate content of the mucilage ranged from 46 to 69 %; thus, carbohydrates were found to represent the major component of taro mucilage, and galactose, mannose and arabinose were identified as the major monosaccharides. Between 30 and 50 % of the mucilage content was protein, and aspartic acid, glutamic acid, glutamine, glycine, leucine, serine, and alanine were the most common amino acids.…”
Section: Introductionmentioning
confidence: 99%